Factor Structure of the Chinese Version of the Parent Adult-Child Relationship Questionnaire - Wang, Daoyang; Dong, Dan; Nie, Peixin; Wang, Cuicui (Frontiers in Psychology, 2018)
The Parent Adult-Child Relationship Questionnaire (PACQ) included two identical versions of the 13-item scale, which were administered to each subject, one which referred to “relationship with mother” and the other to “relationship with father”. The PACQ, originally in English, is a self-report measure of the filial relationship. The present study aimed to develop a Chinese version of the PACQ and use it to explore Chinese parent adult-child relationships. A total of 454 Chinese adult-children completed the Chinese version of the PACQ. The structure of the questionnaire was analyzed using exploratory factor analysis and confirmatory factor analysis. We found that the Cronbach’s α was 0.66–0.88 for fathers and 0.76–0.91 for mothers, which demonstrates high internal consistency reliabilities of the Chinese version of the PACQ. The Chinese version of the PACQ for father had similar constructs similar to with those of the original English version. However, a new factor for mothers, “attachment”, was derived from the original English version. The results suggested that the Chinese version of PACQ is a valid and reliable measure of relationship quality between Chinese adult-children and their parents.